Socioeconomic status, health related behaviour, and self-rated health of children living in Roma settlements in Hungary - Sárváry, Attila; Kósa, Zsigmond; Jávorné, Renáta Erdei; Gyulai, Anikó; Takács, Péter; Sándor, János; Sárváry, Andrea; Németh, Ágnes; Halmai, Réka; Ádány, Róza (Central European journal of public health, 2019)
OBJECTIVE: The poor health of Roma is well documented, but there is only limited data regarding the health of Roma children. The aim of this study was to describe the socioeconomic status, health related behaviour, and health of children living in segregated Roma settlements, and to compare the data with that of non-Roma children. METHODS: In March-April of 2011, a cross-sectional questionnaire-based survey among 11-year-old (211 boys and 252 girls) and 13-year-old (205 boys and 247 girls) children living in Roma settlements was performed (response rate: 91.5%). These data were compared with data from the Health Behaviour in School-Aged Children (HBSC) survey carried out in 2009/2010. RESULTS: The parents of Roma children were substantially less educated and less likely to be actively employed, and Roma children reported lower material welfare than non-Roma ones. The prevalence of consuming sweets and soft drinks at least 5 times per week was 1.5-2 times higher among Roma children. The prevalence of regular intense physical activity was higher at the age of 13 years among Roma boys, while physical inactivity was substantially higher in both age groups among Roma girls. Almost one quarter of Roma children and approximately 14% of non-Roma children had tried smoking at the age of 11. More Roma boys tried alcohol at the age of 11 than non-Roma ones. One in ten Roma children was obese in both age groups. The self-rated health status of Roma children was worse than that of non-Roma children. CONCLUSIONS: Children living in Roma settlements reported poorer socioeconomic conditions, higher consumption of sweets and soft drinks, earlier smoking and alcohol initiation, and worse self-rated health, but with some exceptions do not differ in fruit or vegetable consumption and BMI from general child population. To promote health of children living in Roma settlements, a multi-sector approach, special health education, plus social and health promotion programmes are needed.
Keywords: Surveys and Questionnaires; zdravotní stav; Humans; zdravotnické přehledy; dítě; socioekonomické faktory; prevalence; Child; Alcohol Drinking; pití alkoholu; Female; Romové; Residence Characteristics; zdravé chování; lidé; Roma; Hungary; průzkumy a dotazníky; Socioeconomic Factors; Maďarsko; health behaviour; charakteristiky bydlení; společenská třída; Roma children; ženské pohlaví; Health Status; Male; Adolescent; Cross-Sectional Studies; Prevalence; Health Surveys; Smoking; Social Class; mužské pohlaví; kouření; průřezové studie; mladiství; Health Behavior